Poezja i proza w dziale "Regionalia lubuskie" "Filologii Polskiej" w latach 2015-2025. Podsumowanie = Poetry and prose in the "Lubusz Land - Regional Materials?" section of "Filologia Polska" ["Polish Philology"] in the years 2015-2025. Summary - Szott, Mirosława (1987- ) (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article presents a summary of the ten years of "The Lubusz Land - regional materials" section in the annual "Filologia Polska". The author focuses on literary texts, including presented poetry and prose. She also tracks the subsequent careers of the authors in terms of published books and received awards. Among the contributors whose works have been published in the pages of the yearbook, the following authors appear: Roksana Bach, Michał Banaszak, Rafał Brasse, Edward Derylak, Elżbieta Dybalska, Jolanta Fainstein, Krzysztof Fedorowicz, Agnieszka Gadzińska-Grądkiewicz [Tymoszczuk], Agnieszka Ginko, Dorota Grzesiak, Jerzy Hajduga, Romuald Marek Jabłoński, Beata Patrycja Klary, Barbara Konarska, Elżbieta Kościucha-Wieczorek, Andrey Kotin, Marek Krukowski, Mirosław Kuleba, Eugeniusz Kurzawa, Agnieszka Leśniewska, Marcin Mielcarek, Anna Naplocha, Mieczysław Ostrowski, Aldona Reich, Alfred Siatecki, Czesław Sobkowiak, Anna Staszczuk, Izabela Taraszczuk, Jacek Uglik, Marek Lobo Wojciechowski, Konrad Wojtyła.
Keywords: regionalia lubuskie; poezja; proza; regional materials; Lubusz Land; poetry; prose